Characterization of specific CD4 and CD8 T-cell responses in QuantiFERON TB Gold-Plus TB1 and TB2 tubes. (December 2018) - Allen, Nadia PC.; Swarbrick, Gwendolyn; Cansler, Meghan; Null, Megan; Salim, Hiam; Miyamasu, Misato; Howard, Jenny; Boyle, Jeffrey; Lewinsohn, David; Lewinsohn, Deborah
Abstract: The new generation of the IGRA QuantiFERON-TB Gold Plus (QFT-Plus) includes two antigen tubes, TB1 and TB2 which contain specific Mycobacterium tuberculosis peptides designed to stimulate both CD4 and CD8 T-cells. TB1 is designed to target cell mediated responses from CD4 T-cells, while TB2 contains newly designed peptides designed to also stimulate CD8 T-cells. We identified specific CD4 and CD8 T-cell clones that recognize different regions spanning the length of the CFP-10 protein in M. tuberculosis to directly test in QFT-Plus TB1 and TB2 tubes, followed by Interferon-gamma detection by the QFT-Plus ELISA. These clones showed specific responses to the different QFT-Plus tubes, the CD4 T-cell clone showed dose-dependent responses to both TB1 and TB2 tubes, while the CD8 T-cell clones showed specific and targeted responses to the QFT-Plus TB2 tube (>140-fold difference) versus the QFT-Plus TB1 tubes using the QFT-Plus ELISA. This testing provides direct evidence of the specificity of CD8 T-cell mediated response in QFT-Plus TB2 tubes.